ESI with a gender perspective in University Teacher Training: voices of students of university teaching staff (Praxis Educativa, 2024)
The purpose of this work is to share some of the progress made in a line of research, which is part of a master's degree in Gender, Societies and Public Policies (FLACSO), in which we sought to investigate what meanings in relation to ESI from a gender perspective are expressed by students and teachers in the training field, a common space that brings together students from the Faculty of Human Sciences and Exact and Natural Sciences (UNLPAm) in the period 2021/2022. A qualitative research was chosen, which allows to interpret constructed meanings, enable multiple perspectives and offers the possibility of working from various frames of reference. To construct data, we worked with teaching plans, programs and proposals; interviews with teachers, and opinion surveys and group interviews with students. These student voices share this writing.
Keywords: Comprehensive Sexual Education, gender perspective, modern colonial sex-gender system, university teacher training